The Effect Of Digital Skills And Digital Knowledge On The Performance Of Micro-Enterprise Actors In The Culinary Sector In Cilegon City Through Entrepreneurial Spirit As A Mediation Variable - Hafidz, Hafidz; Wiguna, Wahyu; Suparmoko, Muhammad (Jurnal Economic Resource, 2025)
Culinary MSMEs in Cilegon City play a crucial role in the regional economy, but the low digital skills and digital knowledge of business actors pose a challenge in today's technological developments. This study aims to determine the extent of influence of digital skills and digital knowledge on business actor performance, with entrepreneurial spirit as a mediating variable. The research method used is quantitative with a causal approach. The study population consisted of 3,681 business actors, with a sample of 120 respondents taken using the technique. cluster area sampling. Data were collected through a questionnaire with a Likert scale of 1-5 and analyzed using Structural Equation Modelling (SEM) based Partial Least Square (PLS). The results of the study indicate that digital skills and entrepreneurial spirit have a direct positive and significant effect on performance. Digital knowledge does not have a significant direct effect on performance. Digital skills do not have a significant effect on entrepreneurial spirit), but digital knowledge has a positive and significant effect on entrepreneurial spirit. Entrepreneurial spirit does not mediate the relationship between digital skills and performance, but mediates the relationship between digital knowledge and performance. In conclusion, improving digital skills and digital knowledge accompanied by strengthening the entrepreneurial spirit can be an effective strategy to boost the performance of micro-entrepreneurs in the culinary sector in Cilegon City.